The Influence of Digital Campaigns on Public Perception in the Law Enforcement Process in Society - Valiyah, Naila; Fitri, Dwi; Muqniyanti, Anis; Sari, Deva Permata; Mutiara, Cut; Sari, Nurhidayah; Tanjung, Syakira Adinda Dwi; Elyasa, Eca; Husna, Tasya Ul (Indonesian Journal of Education and Social Humanities, 2025)
Digital campaigns have become an effective strategy in influencing public perception about legal issues and law enforcement. This research uses a literature study and case analysis of digital campaigns related to law enforcement. This study aims to analyze the influence of digital campaigns on public perception in the law enforcement process. The results show that digital campaigns can influence public perception about law enforcement by increasing awareness of the community about legal issues, as well as promoting transparency and accountability in the law enforcement process. However, digital campaigns can also have negative impacts if not conducted properly, such as spreading inaccurate information or manipulating public opinion. Therefore, it is crucial to conduct digital campaigns in an ethical and responsible manner to ensure that public perception about law enforcement is accurate and fair.